Group Guidance Services : A Literature Review of Social Skills Improvement of Elementary School Students - Irfan Fauzi; Yusi Riksa Yustiana (Jurnal Paedagogy, 2024)
This study aims to analyze various studies related to group guidance services and the improvement of social skills of elementary school students. This study used the systematic literature review method with a qualitative approach. This study used bibliometric analysis using VOSviewer software by reviewing research sourced from DOAJ and Google Scholar. The results of the analysis from VOSviewer showed that the issues and trends of group guidance services research had been carried out by researchers in various fields of guidance and counseling and carried out at various levels of education. The findings of various studies showed that group guidance services were seen as having a positive impact on improving the social skills of elementary school students. In the implementation of group guidance services, the role of the leader (counselor) must be active in encouraging the involvement of group members both in group dynamics and in social interactions. The process in this group guidance service will encourage students to achieve the expected goals and also be a means of improving their social skills. This research can be a reference in the implementation of basic group guidance services in improving students' social skills, especially in elementary schools. Guidance and counseling teachers/counselors and teachers in elementary schools can implement group guidance services to improve social skills.